Characteristics, risk factors, and outcomes of neutropenia after liver or kidney transplantation in children. (7th September 2021) - Jarasvaraparn, Chaowapong; Choudhury, Shelley; Rusch, Courtney; Nadler, Michelle; Liss, Kim H. H.; Stoll, Janis; Hmiel, Stanley; Khan, Adeel; Doyle, Maria; Kulkarni, Sakil
Abstract: Background: While prior adult studies have shown that approximately 20%–38% of subjects undergoing solid‐organ transplant develop neutropenia, similar analyses in pediatric subjects are scarce. Methods: We conducted a retrospective chart review of liver transplant (LT) and kidney transplant (KT) recipients at our center during the period 2008–2018. All of the KT and none of the LT subjects during this time period had induction with either anti‐thymocyte globulin (ATG) or basiliximab at time of transplant. Neutropenia was defined as absolute neutrophil count (ANC) value ≤1000/mm 3 . Results: One hundred subjects with LT and 82 subjects with KT were included. The incidence of neutropenia within the first year of transplant in KT was higher compared to LT (54.8% vs 39%, p  = .01). The median number of hospitalizations ( p  = .001) and infectious complications ( p  = .04) was significantly higher only in the KT subjects who developed neutropenia (compared to those who did not). Multivariate analysis identified factors associated with severity of liver disease at transplant, namely h/o upper gastrointestinal bleeding ( p  = .02), weight deficit ( p  = .01), and pre‐LT ANC ( p  = .01), along with high or moderate risk cytomegalovirus status ( p  = .05) as predictors of neutropenia in LT subjects. Female gender ( p  = .03) predicted neutropenia, while BK virus infection was protective for neutropenia ( p  = .04) in KT subjects. Conclusions: The incidence of and morbidity associated with neutropenia within 1 year post‐transplant is higher in KT subjects compared to LT subjects. The likely reason for this is the use of induction therapy (ATG, basiliximab) at the time of transplant in KT subjects.